Effect of Sphaerococcus Coronopifolius Stackhouse 1797 on Anxiety-like Behavior induced by Sciatic Nerve Ligation in Female Wistar Rats - FAHIMA FELLAH; REDHA DJENIDI; AICHA DEHBI-ZEBBOUDJ; HACÈNE FRIH; BELYNDA KERDOUCHE (International Journal of Pharma and Bio Sciences, 2018)
The aim of this study was to investigate the anxiolytic-like effect of phenolic extract of the red algae Sphaerococcus coronopifolius in female Wistar rats. Anxiety was induced by sciatic nerve ligation. A daily intra-peritoneal injections of 25mg algae extract kg−1 bodyweight of rat were administered for two weeks, at the same time. Open field (OF), elevated plus-maze (EPM), and forced swimming (FS) tests were performed to evaluate locomotor activity, anxiolytic and antidepressant effects of the extract. After behavioral tasks, spleen and adrenal glands were removed for histopathological studies. The results showed that the sciatic nerve ligation caused a depression-like behavior in female rats, as indicated by the significant increase in immobility time in the forced swimming test in contrast with the algae extract which demonstrated an antidepressant-like activity. The results obtained in the open field and in the elevated plus maze assays showed a preserved spontaneous locomotion and an anxiolytic-like activity. The treated group with algae extract showed normal structure in histological pictures.